2118. Heathcare-Associated Infection in Intensive Care Patients Infected and Non-infected by Human Immunodefficiency Virus. (26th November 2018) - Castro-Lima, Victor; Borges, Igor; Joelsons, Daniel; Sales, Vivian; Guimarães, Thaís; Li, Ho Yeh; Costa, Silvia; Moura, Maria Luisa Do Nascimento
Abstract: Background: Healthcare-associated infections (HAI) are related with high mortality and emergence of multidrug-resistant (MDR) organisms, mainly in critical care patients. Human immunodeficiency virus (HIV) infection is a frequent cause of intensive care unit (ICU) admission, but data about HAI in this population is scarce. We aimed to evaluate HAI mortality in patients infected and non-infected by HIV in an ICU in a Brazilian public hospital and describe their epidemiological and microbiological characteristics. Methods: This retrospective cohort included patients admitted in an Infectious Diseases ICU from July 2013 to December 2017 who acquired HAI. A database was created using SPSS and multivariate analysis was performed. Primary outcome was 30-day mortality after onset of infection. Secondary outcomes were infection caused by MDR organisms and device-associated HAI. Results: During the study period, 77 ICU-patients (25 HIV and 52 non-HIV) acquired 106 HAI. HIV-patients were younger than non-HIV (45 vs. 58 years old, P = 0.002) and had more respiratory distress at admission (60.0% vs. 34.6%, P = 0.035). There was a high 30-day mortality and no difference among groups (HIV 52.0% vs. non-HIV 54.9%, P = 0.812), which was confirmed after adjusting for age, sequential organ failure assessment (SOFA) score in the day of HAI, MDR infection and more than one HAI. Central-line associated bloodstream infections (CLA-BSI) was the most frequent HAI in general population (39.6%), moreover, ventilator-associated pneumonia (VAP) was more frequent in HIV group (45.2% vs. 26.7%, P = 0.063), with similar period of invasive devices. Enterococcus faecalis was the most frequent cause of CLA-BSI in HIV group (30.0%), while Klebsiella pneumoniae was in non-HIV group (28.1%). Acinetobacter baumannii and K. pneumoniae (each 35.7%) were the predominant agents of VAP in HIV group, as Pseudomonas aeruginosa (35.0%) was in non-HIV group. Although there was a high frequency of HAI caused by MDR organisms, there was no difference among the groups (HIV 77.8% vs. non-HIV 64.3%, P = 0.214). Conclusion: HIV was not associated with higher mortality in critical care patients who acquired HAI. VAP was more frequent in HIV patients, probably due to higher prevalence of respiratory conditions at admission. Infection by HIV does not increase the chance to acquire an HAI by MDR organism. Disclosures: All authors: No reported disclosures.